2016
DOI: 10.1212/wnl.0000000000003362
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell and endothelial cell damage in transthyretin familial amyloid polyneuropathy

Abstract: These findings suggest that direct insult of amyloid fibrils causes Schwann cell damage, resulting in the predominant loss of small-fiber axons characteristic of early-onset cases. In addition, vasculopathy may participate in the pathogenesis of neuropathy, particularly in late-onset cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 39 publications
1
117
0
2
Order By: Relevance
“…A previous study showed extensive nerve fiber loss despite small amount of amyloid deposition in late-onset FAP patients from non-endemic areas, indicating that pre-fibrillar TTR aggregates may participate in fiber degeneration in such patients [47]. In contrast, a recent study indicated that direct insult of amyloid fibrils caused Schwann cell damage, leading to nerve fiber loss, in early-onset FAP patients from endemic foci [48]. All together, these data contributes to the hypothesis that also macrophage phenotype and function may be differently modulated depending on the onset and patient endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed extensive nerve fiber loss despite small amount of amyloid deposition in late-onset FAP patients from non-endemic areas, indicating that pre-fibrillar TTR aggregates may participate in fiber degeneration in such patients [47]. In contrast, a recent study indicated that direct insult of amyloid fibrils caused Schwann cell damage, leading to nerve fiber loss, in early-onset FAP patients from endemic foci [48]. All together, these data contributes to the hypothesis that also macrophage phenotype and function may be differently modulated depending on the onset and patient endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, loss of tight junctions and the fenestration of endothelial cells, as well as other changes in endotelial cell mophology and number, were recently identified as common pathological finding by electron microscopy in sural nerve biopsies from patients with ATTR amyloidosis. 7 Of note, spondilogenic radiculopathies and lumbar canal stenosis were also frequently suspected before the diagnosis of ATTR amyloidosis and a not negligible proportion of these patients underwent spine surgery with partial or no benefit. These data should encourage to raise awareness in neurosurgeons and orthopaedic surgeons about the possibility of ATTR amyloidosis in patients with sensory disturbances and progressive motor deficit at lower limbs, particularly in association with bilateral carpal tunnel syndrome.…”
mentioning
confidence: 99%
“…50 In a study of 165 ATTRm amyloidosis patients carrying the mutation Val30Met, HRV was reduced in 47%. 53 Additionally, Schwann cell atrophy and disruption of the blood-nerve barrier can be found. Biopsy of the sural nerve is less sensitive because amyloid deposition is often patchy.…”
Section: Autonomic Testingmentioning
confidence: 99%